2004
DOI: 10.1128/jb.186.11.3547-3560.2004
|View full text |Cite
|
Sign up to set email alerts
|

The ETT2 Gene Cluster, Encoding a Second Type III Secretion System from Escherichia coli , Is Present in the Majority of Strains but Has Undergone Widespread Mutational Attrition

Abstract: ETT2 is a second cryptic type III secretion system in Escherichia coli which was first discovered through the analysis of genome sequences of enterohemorrhagic E. coli O157:H7. Comparative analyses of Escherichia and Shigella genome sequences revealed that the ETT2 gene cluster is larger than was previously thought, encompassing homologues of genes from the Spi-1, Spi-2, and Spi-3 Salmonella pathogenicity islands. ETT2-associated genes, including regulators and chaperones, were found at the same chromosomal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
156
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(168 citation statements)
references
References 64 publications
(73 reference statements)
11
156
1
Order By: Relevance
“…The ETT2 locus in 7122 and IMT2125 is truncated from within eivA to the end of the locus described for E. coli O157:H7 strain Sakai, consistent with the truncation described for another sepsis-associated APEC O78 strain, termed 789 (30). Within ETT2, the predicted spaS and eivJ genes contain distinct frameshift mutations in 7122 and IMT2125, consistent with the varied patterns of mutational attrition of the locus reported among E. coli strains (30,63). The ymcDCBA-yccZ-etp-etk genes, which determine O-antigen capsule biosynthesis (located between appA and yccM) (64), were conserved in both 7122 and IMT2125 but absent in APEC O1.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The ETT2 locus in 7122 and IMT2125 is truncated from within eivA to the end of the locus described for E. coli O157:H7 strain Sakai, consistent with the truncation described for another sepsis-associated APEC O78 strain, termed 789 (30). Within ETT2, the predicted spaS and eivJ genes contain distinct frameshift mutations in 7122 and IMT2125, consistent with the varied patterns of mutational attrition of the locus reported among E. coli strains (30,63). The ymcDCBA-yccZ-etp-etk genes, which determine O-antigen capsule biosynthesis (located between appA and yccM) (64), were conserved in both 7122 and IMT2125 but absent in APEC O1.…”
Section: Resultssupporting
confidence: 54%
“…S1 and S2 in the supplemental material). Among the virulence-associated loci present in 7122 and IMT2125 but absent from APEC O1 is the degenerate type III secretion locus ETT2, located between yqeG and the glyU tRNA locus in many E. coli strains (63). The ETT2 locus in 7122 and IMT2125 is truncated from within eivA to the end of the locus described for E. coli O157:H7 strain Sakai, consistent with the truncation described for another sepsis-associated APEC O78 strain, termed 789 (30).…”
Section: Resultsmentioning
confidence: 64%
“…A technique called tiling-path PCR scanning (TP-PCR), previously described by Ren et al (29), was used with some modifications. Briefly, the method consists of several interlocking PCRbased approaches able to characterize large genomic regions.…”
Section: Methodsmentioning
confidence: 99%
“…To construct a complete tiling path through GI-3 and to determine the genetic organization within the island for the 69 strains, we used the TP-PCR method (29), which exploits short-and long-PCR protocols; this method allowed us to construct a complete tiling path through the GI-3 gene cluster for 69 strains and for type strain 544. Initially, we confirmed that reference strain 544 possessed GI-3 gene clusters by short and long PCR, first amplifying ORFs BruAb1_0251, BruAb1_0256, BruAb1_0266, and BruAb1_0274 by short PCR (data not shown) and then amplifying fragments A, B, C, and D by long PCR.…”
Section: Gi-3 Is Present In All Isolatedmentioning
confidence: 99%
“…37 Additionally, the ETT2 gene cluster has been identified in the EAEC O42 genome sequence providing evidence for T3SS mechanism prevalence as well. 38 These secretion systems may play a key role in EAEC virulence due to expulsion of toxic proteins and association with biofilm formation; 39 their roles in pathogenesis remain widely unknown. Heterogeneity among EAEC strains remains an overarching issue that complicates elucidating pathogenic mechanisms underlying infection.…”
mentioning
confidence: 99%